EXTRACTION OF TANNINS AND SAPONINS FROM PLANT SOURCES AND THEIR EFFECTS ON In vitro METHANOGENESIS AND RUMEN FERMENTATION - Yuliana, P.; Laconi, E.B.; Wina, E.; Jayanegara, A. (Diponegoro University, 2014)
This study was aimed to extract tannins from Swietenia mahagony and saponins from Sapindusrarak by using different solvents, and to test their extracts on in vitro rumen fermentation andmethanogenesis. Solvents used for extraction were water, methanol, acetone and their combinations.Tannin and saponin extracts were added into each incubation bottle containing Brachiaria humidicolagrass and Indigofera sp. legume (1:1 w/w) according to the following treatments (in four replicates): R1:control substrate, R2: R1 + 0.5 mg/ml tannin extract, R3: R1 + 1 mg/mL tannin extract, R4: R1 + 0.5mg/mL saponin extract, R5: R1 + 1 mg/mL saponin extract, R6: R1 + 0.5 mg/mL tannin extract + 0.5mg/mL saponin extract, and R7: R1 + 1 mg/mL tannin extract + 1 mg/mL saponin extract. Resultsrevealed that 75% water + 25% methanol was the best solvent to extract tannins from S. mahagonywhereas 100% methanol was the best to extract saponins from S. rarak. The highest gas production andthe lowest methane emission were obtained in R7. It can be concluded that combination of tannin andsaponin extracts were potential in mitigating ruminal methane emissions.